II. Abdülhamid’e Kitapla ŞantajAlman Gazeteci Julius Grosser TarafındanYazılması Tasarlanan Kitabın Hikâyesi - KON, KADİR (My University, 2024)
Bu makalede Alman gazeteci Dr. Julius Grosser’in 1895 yılında Babıâli’ye sunduğu bir kitap taslağı etrafında gelişen olaylar ele alınmaktadır. Fransızca yazılmış ve esasında şantaj amaçlı olan kitap taslağı “Hamidî Rejim”e ve onunla iş birliği yapan Türkiye’deki Alman uzmanlara ağır suçlamalarda bulunmaktadır. Bu yönüyle kitap, o dönemde Türkiye’deki nüfuzunu oldukça artırmış olan Almanya’nın Osmanlı devleti ile ilişkilerini bozma potansiyelini de barındırmaktadır. Öte yandan Tanzimat reformlarıyla birlikte Batı kamuoyunda olumlu imaj oluşturmayı uluslararası sistemde meşru bir zemin sağlamanın yolu olarak gören Osmanlı devletinin “medeni” olma çabasına zarar verecek böyle bir girişim karşısında Babıâli’nin ve Yıldız Sarayı’nın tavrı önem kazanmaktadır. Makalede Ajans de Konstantinopel’in sahibi olan Dr. Julius Grosser’in ve sonradan onun davasını ve işini devralacak olan karısı Anna Grosser-Rilke’nin faaliyetleri Osmanlı arşiv belgelerinden takip edilmiştir. Böylece bahsi geçen haber ajansı örneğinden hareketle II. Abdülhamid idaresinin yabancı haber ajanslarına yönelik tutumunun anlaşılmasına katkı sunulması da amaçlanmıştır. Anahtar Kelimeler: Dr. Julius Grosser, Anna Grosser-Rilke, II. Abdülhamid, Kitap, Şantaj, Yabancı Haber Ajansları

This article discusses the events surrounding a book draft submitted to the Porte by German journalist Dr. Julius Grosser in 1895. The draft, which was written in French and was essentially intended as blackmail, makes heavy accusations against the “Hamidian Regime” as well as the German experts in Turkey who collaborated with the Regime. In this respect, the book had the potential to distrupt the Ottomans’ relations with Germany, which had increased its influence in Turkey considerably. On the other hand, it is important to notice the manner in which the Sublime Porte and Yıldız Palace took a stand in the face of such an initiative that would have harmed the Ottoman state’s efforts to be “civilized,” with the attempt to foster a positive image in the Western public opinion with the Tanzimat reforms, so as to gain a legitimate ground in the international system. This article traces the activities of Dr. Julius Grosser, the owner of the Agence de Constantinople, and his wife Anna Grosser-Rilke, who would later take over his cause and business, through Ottoman archival documents. Thus, it also aims to contribute to the understanding of the attitude of the Abdülhamid II administration towards foreign news agencies with reference to the example of the aforementioned agency. Keywords: Dr. Julius Grosser, Anna Grosser-Rilke, Abdulhamid II, Book, Blackmailing, Foreign News Agencies, Agence de Constantinople
Keywords: Dr. Julius Grosser; Anna Grosser-Rilke; Abdulhamid II; Book; Blackmailing; Foreign News Agencies; Agence de Constantinople; II. Abdülhamid; Kitap; Şantaj; Yabancı Haber Ajansları